Ciliate community structure and interactions within the planktonic food web in two alpine lakes of contrasting transparency. (November 2016) - Kammerlander, Barbara; Koinig, Karin A.; Rott, Eugen; Sommaruga, Ruben; Tartarotti, Barbara; Trattner, Florian; Sonntag, Bettina
Summary: Climate warming is accelerating the retreat of glaciers and recently, many 'new' glacial turbid lakes have been created. In the course of time, the loss of the hydrological connectivity to a glacier causes, however, changes in their water turbidity and turns these ecosystems into clear ones. To understand potential differences in the food‐web structure between glacier‐fed turbid and clear alpine lakes, we sampled ciliates, phyto‐, bacterio‐ and zooplankton in one clear and one glacial turbid alpine lake, and measured key physicochemical parameters. In particular, we focused on the ciliate community and the potential drivers for their abundance distribution. In both lakes, the zooplankton community was similar and dominated by the copepod Cyclops abyssorum tatricus and rotifers including Polyarthra dolichoptera, Keratella hiemalis, Keratella cochlearis and Notholca squamula . The phytoplankton community structure differed and it was dominated by the planktonic diatom Fragilaria tenera and the cryptophyte alga Plagioselmis nannoplanctica in the glacial turbid lake, while chrysophytes and dinoflagellates were predominant in the clear one. Ciliate abundance and richness were higher in the glacial turbid lake (∼4000–27 800 Ind L −1, up to 29 species) than in the clear lake (∼570–7150 Ind L −1, up to eight species). The dominant species were Balanion planctonicum, Askenasia cf. chlorelligera, Urotricha cf. furcata and Mesodinium cf. acarus . The same species dominated in both lakes, except for Mesodinium cf. acarus and some particle‐associated ciliates, which occurred exclusively in the glacial turbid lake. The relative underwater solar irradiance (i.e. percentage of PAR and UVR at depth) significantly explained their abundance distribution pattern, especially in the clear water lake. In the glacial turbid lake, the abundance of the dominating ciliate taxa was mainly explained by the presence of predatory zooplankton. Our results revealed an unexpected high abundance and richness of protists (algae, ciliates) in the glacial turbid lake. This type of lake likely offers more suitable environmental conditions and resource niches for protists than the clear and highly UV transparent lake.